2009
DOI: 10.1007/s11240-009-9661-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro root culture of Ocimum sanctum L. and evaluation of its free radical scavenging activity

Abstract: Young leaf explants of Ocimum sanctum L. incubated on solidified Murashige and Skoog (MS) medium supplemented with 2 mg l -1 1-naphthaleneacetic acid (NAA) and 0.2 mg l -1 kinetin (Kn) developed rhizogenic callus. When these were subcultured onto MS medium supplemented with 1.5 mg l -1 2, 4-dichlorophenoxyacetic acid (2, 4-D) and 0.5 mg l -1 NAA, friable rhizogenic callus was observed. Upon transfer of this friable callus onto liquid MS medium containing 4 mg l -1 NAA and 1.3 mg l -1 6-benzyladnine (BA) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…In the present study, however, no such inhibitory effect of cytokinins was noticed and production of healthy fasciculated roots took place under the combined influence of BA and Kn. Reports published earlier have demonstrated that Kn promotes the development of roots (Hill and Lawrence 1985) and a low dose of Kn in combination with NAA has been found to be highly conducive for induction of roots from young leaf explants of Ocimum sanctum (Shilpa et al 2010). Our reports are also in agreement with the previous reports describing the promotive effects of BA and Kn on root growth and proliferation.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, however, no such inhibitory effect of cytokinins was noticed and production of healthy fasciculated roots took place under the combined influence of BA and Kn. Reports published earlier have demonstrated that Kn promotes the development of roots (Hill and Lawrence 1985) and a low dose of Kn in combination with NAA has been found to be highly conducive for induction of roots from young leaf explants of Ocimum sanctum (Shilpa et al 2010). Our reports are also in agreement with the previous reports describing the promotive effects of BA and Kn on root growth and proliferation.…”
Section: Resultssupporting
confidence: 93%
“…The production of annatto pigment from normal root cultures that has been reported in this study is unique compared with the other root cultures reported to produce secondary metabolites, such as Hemidesmus indicus (Sreekumar et al 1998), Decalepis hamiltonii (Giridhar et al 2005), Angelica gigas (Rhee et al 2010), and antioxidant activity as in the case of Ocimum sanctum (Shilpa et al 2009). Similarly, liposoluble pigments from edible roots of Beta vulgaris (Kolesnik et al 1989) and localization of carotenoids in roots of graminaceous plants (Klingner et al 1995) were previously known.…”
mentioning
confidence: 53%
“…Regenerated plantlets are able to accumulate secondary metabolites similar to those found in the mother plant (Shilpa et al 2010). The antioxidant potential of the regenerated tissues of P. nigrum was determined using the DPPH8 free radical (Fig.…”
Section: Gibberellic Acid á Organogenesis á Piper Nigrummentioning
confidence: 99%